The encyclopedia of war journalism, 1807-2010 - Roth, Mitchel P., 1953- (Grey House Pub., 2010)
Examines the development, history and current state of war journalism from the Mexican War in 1846 to the current Conflicts in the Middle East. Provides a unique, around the world look at how conflicts were covered and explores the influences of the flow of information on the battlefield and the home front.